Cultural recognition for women with diabetes using alternative health care in Malay Ethnic, West Kalimantan, Indonesia: A focused ethnography - Parliani; Pearkao, Chatkhane (Belitung Nursing Journal, 2026)
Background: The use of alternative health care among people with diabetes remains widespread, especially in rural areas of West Kalimantan, Indonesia. In the Malay ethnic community, alternative health care is not just an issue of access but also deeply rooted in cultural and spiritual practices. However, limited research has explored the symbolic meanings and socio-cultural dynamics that underlie the consistent use of alternative health care by people with diabetes. Objective: This study aimed to explore the cultural recognition and socio-cultural meanings embedded in the use of AHC among Malays with diabetes in West Kalimantan, Indonesia. Methods: A focused ethnography was conducted from July to November 2024 using in-depth interviews, focus group discussions (FGDs), observations, and field notes. A total of 45 participants took part in interviews, including people with diabetes, healthcare providers, traditional healers (Tabib), family members, healthcare volunteers, and community leaders. FGDs comprised five groups, and observations included nine participants. Data were analyzed through content, typology, and matrix analysis. To ensure trustworthiness, triangulation and member checking were employed. The study was guided by three theoretical frameworks: Symbolic Interactionism, Cultural Theory, and Critical Social Theory. Findings: Four main themes emerged: (1) cultural logic and illness meaning, in which illness was viewed as a spiritual and moral imbalance; (2) symbolic meanings in alternative health care practices, highlighting ritual healing and spiritual faith; (3) social structures as pillars of healing, where family and community roles legitimized alternative health care; and (4) social processes that created cultural recognition through intergenerational transmission and community validation. Conclusion: Recognizing AHC culturally is essential for understanding the illness experiences of people with diabetes. For nursing practice, these findings emphasize the importance of providing culturally respectful care, fostering open communication between healthcare providers and people with diabetes, and incorporating alternative healthcare approaches into safe, evidence-based health education.